THE INFLUENCE OF MARKET RESEARCH, CONSUMER BEHAVIOR AND WORD OF MOUTH COMMUNICATION FOR SUSTAINABLE MARKETING OF ELECTRIC VEHICLE IN INDONESIA - Lestari , Dhoya Safira Tresna; Quddoos, Muhammad Umer (PT. Jurnal Center Indonesia Publisher, 2025)
The rapid transition to electric vehicles (EV) is driven by global environmental concerns and the need to reduce dependence on fossil fuels. In Indonesia, EV adoption faces challenges related to market dynamics, consumer behavior, and effective communication strategies. Marketing research and understanding consumer behavior aims to collect and obtain more detailed information and knowledge about customers towards electric vehicle products. Through this, it can understand customers and their tastes, preferences, reflect the future, and also help reduce the risk of product and business failure. Using Word of Mouth communication as part of a marketing strategy that can be carried out by companies in maintaining their business desires. In this article, the author tries to understand the concept of market research, consumer behavior, and the Word-of-Mouth communication model using a qualitative library observation approach, this study analyzes existing research on how these three factors contribute to the growth and long-term survival of the electric vehicle market. Market research provides insight into consumer preferences and market trends, offering important data to align EV products with consumer needs. Understanding consumer behavior is essential in overcoming perceived barriers, such as cost and infrastructure limitations, that hinder EV adoption. Meanwhile, word of mouth communication plays an important role in influencing consumer decisions by fostering trust and awareness of the benefits of EVs. The findings highlight the interconnections between these factors and their collective impact on the development of sustainable marketing strategies for EVs in Indonesia. This study provides valuable insights for stakeholders, including automotive companies and policymakers, in designing more effective marketing approaches that support the sustainable growth of the EV sector.